Sport specialization, injury and illness: a prospective study of elite female adolescent soccer players - Watson, A.; Haraldsdottir, K. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Although cross-sectional evidence exists regarding the association between sport specialization and health outcomes, sport-specific, prospective research is lacking. The aim of this study was to determine the relationship between sport specialization status and in-season injury and illness risk in elite female adolescent soccer players.